Применение уличных опросов в исследованиях электоральных ориентаций - Мищенко, М. (Социология: теория, методы, маркетинг, 2006)
Studying the electoral orientations a researcher may be faced with the lack of sincerity shown by respondents that causes errors. For the improvement of results in sociological research it is necessary to provide a feeling of anonymity that contributes to a higher sincerity of respondents. Street survey can be considered as one of the possible methods of sociological research, which allows to achieve this goal. Comparing the results of two surveys made by different methods (in the street and living quarters), the author analyzes their advantages and drawbacks.